Chronic Migraine and Accelerated Brain Ageing: A Focus on Hippocampal Atrophy - Choudhary, Dr. Arbind Kumar (Medical Research Archives, 2025)
Chronic migraine (CM) is increasingly recognized as more than just a recurring headache condition. It involves significant neurobiological changes that suggest accelerated aging of the brain, particularly affecting the hippocampus, which is essential for memory and cognitive functions. This overview examines the key findings linking CM to notable decreases in cortical thickness, increased white matter hyperintensities, and significant hippocampal atrophy. Research utilizing machine learning in neuroimaging has introduced the concept of the Brain Age Gap (BAG). This concept reveals that individuals with CM have an average brain age that is 4.16 years older than their chronological age, indicating premature aging of their neural structures. These structural changes are associated with difficulties in declarative memory, disruptions in memory-encoding processes, and higher rates of depression and anxiety. Factors such as neuroinflammation, ongoing pain signals, and related health conditions such as obesity and hypertension worsen this neurodegenerative trajectory. The growing body of evidence highlights the urgent need for early identification of at-risk individuals, validation of BAG as a potential cognitive health biomarker, and development of targeted interventions to prevent cognitive decline. To confirm these findings, prospective long-term studies are crucial to confirm the patterns of hippocampal atrophy and to establish effective imaging techniques for migraine management.